Primary pulmonary angiosarcoma was misdiagnosed as IgG4-related disease by needle biopsy: A challenging case report - Shufei Wei; Yongliang Han; Yingyong Hou; Jiali Hu (Indian Journal of Pathology and Microbiology)
Angiosarcoma is a rare soft tissue sarcoma. Primary angiosarcoma of the lung is even rarer. This case presents a patient with hemoptysis for 3 months. A chest computed tomography (CT) showed multiple patches of nodules with peripheral exudates distributed along the vascular bundles in both lungs, and the biopsy suggested IgG4 disease. However, the hemoptysis worsened for 3 days, and the patient underwent partial resection of the left upper lung, revealing eight masses of 0.5–2 cm in diameter. The tumor was composed of spindle, round, or polygonal cells arranged in bundles or sheets, and tumor cells were positive for vascular tumor markers. The patient was treated with six cycles of paclitaxel combined with gemcitabine chemotherapy, reducing the volume of the masses and improving hemoptysis.